Glial cells modulate the synaptic transmission of NTS neurons sending projections to ventral medulla of Wistar rats - Accorsi-Mendonça, Daniela; Zoccal, Daniel Breseghello [UNESP]; Bonagamba, Leni G. H.; Machado, Benedito H. (The American Physiological Society and the Physiological Society, 2013)
There is evidence that sympathoexcitatory and respiratory responses to chemoreflex activation involve ventrolateral medulla-projecting nucleus tractus solitarius (NTS) neurons (NTS-VLM neurons) and also that ATP modulates this neurotransmission. Here, we evaluated whether or not astrocytes is the source of endogenous ATP modulating the synaptic transmission in NTSVLM neurons. Synaptic activities of putative astrocytes or NTS-VLM neurons were recorded using whole cell patch clamp. Tractus solitarius (TS) stimulation induced TS-evoked excitatory postsynaptic currents (TS-eEPSCs) in NTSVLM neurons as well in NTS putative astrocytes, which were also identified by previous labeling. Fluoracetate (FAC), an inhibitor of glial metabolism, reduced TS-eEPSCs amplitude ( 85.6 16 vs. 39 7.1 pA, n = 12) and sEPSCs frequency (2.8 0.5 vs. 1.8 0.46 Hz, n = 10) in recorded NTSVLM neurons, indicating a gliomodulation of glutamatergic currents. To verify the involvement of endogenous ATP a purinergic antagonist was used, which reduced the TS-eEPSCs amplitude ( 207 50 vs. 149 50 pA, n = 6), the sEPSCs frequency (1.19 0.2 vs. 0.62 0.11 Hz, n = 6), and increased the paired-pulse ratio (PPR) values (~20%) in NTS-VLM neurons. Simultaneous perfusion of Pyridoxalphosphate-6-azophenyl-2′,5′-disulfonic acid (iso-PPADS) and FAC produced reduction in TS-eEPSCs similar to that observed with iso-PPADS or FAC alone, indicating that glial cells are the source of ATP released after TS stimulation. Extracellular ATP measurement showed that FAC reduced evoked and spontaneous ATP release. All together these data show that putative astrocytes are the source of endogenous ATP, which via activation of presynaptic P2X receptors, facilitates the evoked glutamate release and increases the synaptic transmission efficacy in the NTS-VLM neurons probably involved with the peripheral chemoreflex pathways.
Keywords: Gliotransmission; NTS neurons; Tripartite synapse